2010
DOI: 10.2528/pierc10061401
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of Complicated DRFM Range False Targets via Temporal Pulse Diversity

Abstract: In this paper, a jamming cancelation approach based on the concept of pulse diversity is proposed to suppress some newer complicated digital radio frequency memory (DRFM) range false targets (RFT). Just repeating the intercepted radar electromagnetic signal, as done in the conventional re-transmitting jammer, is not effective because only one range false target is produced. In contrast, the newer DRFM-based RFT generation methods, especially chopping and interleaving (C&I) and smeared spectrum (SMSP) can yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Obviously, the received radar signals in a given slow-time interval contain both current echoes and re-transmitting jamming with respect to the previous pulse. When radar emits pulse with a high repetitive frequency, there are only just slight changes in system geometry over short adjacent periods of slow-time intervals [2], [5]. Under these instances the reflectors normally do not raise a big change and almost remain stationary.…”
Section: Radar and Jamming Signal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the received radar signals in a given slow-time interval contain both current echoes and re-transmitting jamming with respect to the previous pulse. When radar emits pulse with a high repetitive frequency, there are only just slight changes in system geometry over short adjacent periods of slow-time intervals [2], [5]. Under these instances the reflectors normally do not raise a big change and almost remain stationary.…”
Section: Radar and Jamming Signal Modelmentioning
confidence: 99%
“…Two-dimensional frequency domain motion compensation algorithm is used to overcome the limitation of One-dimensional range frequency domain motion compensation and match filtering. Schema in Ref [4] obtains a good performance and fully removes the impact of target motion on matched filtering, However, the paper presented in Ref [5] indicates that, because the pulse signal is processed in base band, the signal sampling rate (uniform sampling is assumed) is then relatively in a lower level. It is confirmed that the error introduced by the time delay difference is likely less than the error introduced in the sampling process.…”
Section: Radar and Jamming Signal Modelmentioning
confidence: 99%
“…When an EA system repeats multiple false targets with high JSR at the same time, however, the model is not feasible for the observed increased occurrence of more amplitudes or spikes in range bins of interest. This leads researchers to expand the algorithms to fit the multiple jammers scenario [8][9][10]. However, the efficiency of the approaches necessitates a reliance on permissions of the waveform agility or complicated code.…”
Section: Introductionmentioning
confidence: 99%
“…Some electronic counter-countermeasures (ECCM) are exploited to suppress the jammer in order to detect desired targets and estimate the target parameters under severe jamming conditions. Among them a technique referred to as pulse diversity, which assumes the victim radar operates with a waveform not currently in use by the jammer, can be used to handle the false target effectively [3,4,5]. This premise is always the case encountered in practice when the jammer attempts to protect targets which are closer to the radar than itself.…”
Section: Introductionmentioning
confidence: 99%